2019
DOI: 10.18510/hssr.2019.7262
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Students’ Decision for Enrolment at Universiti Kuala Lumpur Business School Campus

Abstract: Purpose of Study: This research focuses on factors influence students’ decisions making to enrol at private Higher Education Institution (HEI). Methodology: The underpinning theory applied in this study was Theory of Planned Behavior (TPB) applied for institution rankings, institution facilities, and employment opportunities. Questionnaire was used to collect the data over 100 of students in Universiti Kuala Lumpur, Business School Campus. Data were analyzed by employing exploratory factor analyses and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For example, altruism having a significant negative relationship with CSR toward education in both government and private corporations aligns with previous research findings by Wilhelm and Ribar (2002) that revealed a weak relationship when they tested for altruistic intentions behind donations made by government and private corporations. Reciprocity having a significant positive influence on CSR in education in government corporations aligns with Worth et al (2019), Hassan et al (2019) and Shamsudin et al (2019) who found that donor corporations try to influence critical organizations in their community and try to achieve unanimity in the community related to topics and issues of concern to themselves. The research findings regarding involvement as a significant positive influence on CSR toward education for government and private corporations are also supported by the findings of Worth et al's (2019) whose research had similar findings.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, altruism having a significant negative relationship with CSR toward education in both government and private corporations aligns with previous research findings by Wilhelm and Ribar (2002) that revealed a weak relationship when they tested for altruistic intentions behind donations made by government and private corporations. Reciprocity having a significant positive influence on CSR in education in government corporations aligns with Worth et al (2019), Hassan et al (2019) and Shamsudin et al (2019) who found that donor corporations try to influence critical organizations in their community and try to achieve unanimity in the community related to topics and issues of concern to themselves. The research findings regarding involvement as a significant positive influence on CSR toward education for government and private corporations are also supported by the findings of Worth et al's (2019) whose research had similar findings.…”
Section: Discussionmentioning
confidence: 84%
“…Odendahl (1990) argued that there was a pattern in which most elite donors made donations to causes that were close to their family and social circle and, in return, expected the recipients to reciprocate in the complex network of elites. Dye (1983) suggests that elite networks attempt to influence critical organizations in their community and win elite unanimity related to the concerns and topics of importance to themselves through such social responsibility initiatives (Hassan et al, 2019;Shamsudin et al, 2019).…”
Section: Motivators For Corporate Social Responsibility Toward Educationmentioning
confidence: 99%
“…The second is program-specific factors such as programmes offered, accreditation body, study duration, program content and structure [11,[21][22][23]34]. Reputation is another factor considered, which includes image, reputation, and links with foreign universities [6,11,[17][18][19][20][21][22]24,26]. Next is social factors such as input from family members, peers and social media [6][7][8][9][16][17]19,21,[25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…and campus facilities (dormitories, sports complex, Wi-Fi, etc.) [6,18,20,24,[27][28][29]. Employment prospects and alumni success stories are also considered as one of the factors for IPTS selection [15,[17][18]22,30,34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although these cases of university or knowledge brand cities are evident, no studies were found that empirically defined the perception by the various interest groups of the university city brand. Instead, previous studies only developed the identification of the important factors for the choice of universities and destinations, including public services, specific government policies in science and technology, image, prestige, urban development, and characterisation of the city's groups of influence [22,23].…”
Section: University City Brand Researchmentioning
confidence: 99%